Ethic Economics, Fair Economy, New Economy, Sustainability and other Related Disciplines - Bidabad, Bijan (International Journal of Islamic Business & Management, 2019)
Evolution of humankind in forming economic order of the society passed from caring only individual benefit to looking for social interests. This was what followed in the last millenniums. In this paper, we review this evolutionary process that starts from utilitarianism and reaches to ethical approach in defining human being behavior. It concludes that following what the divine prophets and messengers have understood and legislated are more appropriate for human well-being both in their materialistic and spiritual lives. DOI: https://doi.org/10.5281/zenodo.3402337